News from texts and archaeology: acts of the 7th International Fayoum Symposium, 29 October-3 November 2018 in Cairo and the Fayoum - Römer, Cornelia (Harrassowitz Verlag, 2020)
News from Texts and Archaeology, edited by Cornelia E. Römer, contains twelve of the important papers given at the 7th Fayoum Symposium in Cairo in October/November 2018, most of them dealing with archaeology, some with texts. They mirror the focus of this 7th Symposium, which for the first time took place in Egypt, and which highlighted the archaeological work recently carried out in the Graeco-Roman Fayoum by Egyptian and international missions. Papers include a presentation of the first Hellenistic gymnasium archaeologically attested in Egypt and excavated by the German Archaeological Institute in Cairo, and a catalogue of the Hellenistic and Roman sculptures which come from a secure provenance in the oasis. One paper traces the history of the water-wheel in Egypt, an invention that changed the landscape radically, and shows the sophistication of water supply in the villages in general. Together with the papers on Greek and Demotic texts found in the Fayoum, they all draw a picture of the multi-cultural society of the Egyptian countryside in the Graeco-Roman period. Of special interest are the three maps attached to the volume as an extra, which show the changing levels of the lake in the north of the oasis through the pharaonic and Ptolemaic/Roman periods